State, company, and community relations at the Polaris mine (Nunavut) - Green, Heather (Études/Inuit/Studies, 2013)
AbstractInuit employment in the mining industry has received very little attention from historians, although mining has been in the Arctic since the 1950s. Using the Polaris mine (1982-2002) on Little Cornwallis Island, Nunavut, as a case study, this article focuses on the Canadian government’s shift away from supporting mining developments in the late 1970s to early 1980s, on Inuit employment in the mining industry, and on the difficulties of Inuit from Resolute Bay in obtaining employment at Polaris. Previous to Polaris, the federal government saw Arctic mines, particularly Rankin Inlet (1951-1962) and Nanisivik (1976-2002), as a path to modernisation for the Inuit. However, as these earlier Arctic mines failed in this particular goal, the State became disillusioned and weary of providing financial support by the time Cominco began planning the Polaris mine in 1973. The federal government did not require Cominco to sign a formal agreement for Inuit employment, leaving the company responsible to develop its own hiring agenda. Unfortunately for the people of Resolute Bay, the company agenda did not include hiring locals as a priority, and bypassed and marginalised Resolute Bay Inuit who were keen on working at the mine. As mining has been the largest industry in the Canadian northern economy and is currently growing and beginning new development projects, it is important to understand the historical dynamics between mining companies, the State, and local communities.